Budidaya Tanaman Kacang Tanah (Arachis hypogaea L.) dengan Berbagai Dosis Pupuk Kandang Kotoran Ayam dan Abu Sekam Padi pada Lahan Rawa Lebak - Mariati Mariati; Riyanto Riyanto; Ryan Yurdani; Nur Hafizah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
Cultivation of peanut plants in lebak wetlands is constrained by inundated land and the fertility of varied soil, from fertile to nutrient-poor levels. Poor soil nutrients can not only be overcome by fertilizing, for example with manure chicken manure. The availability of nutrients in the land can be improved by providing ameliorats such as rice husk ash. This study aims to determine the effect of (i) the interaction of chicken manure manure and rice husk ash, (ii) the single factor of chicken manure manure, (iii) the single factor of rice husk ash, (iv) getting the best dose of chicken manure manure, ( v) the best dose of rice husk ash and (vi) the best interaction of manure chicken manure and rice husk ash on lebak wetland. The study was conducted in the village of Teluk Betung, Sungai Pandan Subdistrict, HSU Regency in February - May 2019. It was using a factorial Randomized Block Design (RBD) with two treatment factors. The first factor: the dose of chicken manure, consisting of 3 levels, namely a1 = 12 tons. ha-1, a2 = 16 tons. ha-1, a3 = 20 tons. ha-1. The second factor: the dose of rice husk ash, consisting of 3 levels, namely s1 = 24 tons.ha-1, s2 = 28 tons.ha-1, s3 = 32 tons.ha-1. The results showed that the interaction between chicken manure had no effect on growth and yield, the single factor of chicken manure had an effect on growth and yield but had no effect on the number of leaves, and the single factor of rice husk ash did not affect growth and yield but had an effect on age flowering.